Pepak Bahasa Jawa Multimedia Berbasis Android - Rama Pradestya, Davin; , Aris Rakhmadi, S.T., M. Eng (2017)
Pepak bahasa jawa is an educative dictionary that used to help the user inlearning Javanese Language easier. Nowadays, the use of Javanese language as one of the native language of Indonesia, is being offended by the rush globalization and technology.Javanese language is a means of communication used by society to cooperate, to interact, and to identify among Javanese people. The utilization of the native nguages like Javanese language in Indonesia as the part of culture of this country is more recessive by globalization. refore, interactive learning media is needed to be used as an alternative means to study it. This research takes the issues of how to create interactive learning application presenting the rules of using Javanese language properly by using Android Studio with objective to facilitate users in studying and to make a positive contribution for science and technology. The method of this research is SDLC (System Development Life Cycle).This method begins with collecting the materials of Javanese Language matching with the curriculum, designing the flow chart and the application, adjusting the design by using Android Studio, then testing it on the users (Senior High Students) to obtain the result whether it works properly. The result of this research is a read-only applicationpresenting explanation ofaksara jawa (Javanese characters), pewayangan, sanepan, parikan, tembang and exercise. The application can be running on Android device mobile from 2.3 version(Gingerbread) up to 4.1.2 version (Jelly Bean) and it requires 14.29 MB memory space.